Effect of Soil pH Variation on Peanut Plant Growth - Gusti Rusmayadi; Safruddin Safruddin (Westscience Press, 2024)
This research investigates the qualitative effects of soil pH variation on peanut plant growth, aiming to provide insights into the complex interactions between soil properties and plant responses in agricultural ecosystems. Through semi-structured interviews with ten informants, supplemented by insights synthesized from prior research and theoretical frameworks, the study explores perceived relationships, implications for soil health and nutrient availability, challenges, opportunities, and practical implications for peanut production. Key findings highlight the critical influence of soil pH on peanut growth and productivity, with deviations from optimal pH levels affecting nutrient availability, root health, and overall plant vigor. Participants underscore the importance of targeted soil management practices, including lime application, organic matter incorporation, and crop rotation, in optimizing soil pH and supporting resilient peanut production systems. The study identifies challenges in soil pH management, such as limited accessibility of soil testing services and inadequate farmer knowledge, while also highlighting opportunities for innovation and improvement. The insights gleaned from the study contribute to advancing knowledge in agricultural sciences and inform evidence-based soil management practices for sustainable peanut production.